Effect of Preparatory Information Provision Program on Anxiety in the Patients Undergoing Brain Tumor Surgery - pasethakung, wanwisa; Phutthikhamin, Nichapatr (Journal of Thailand Nursing and Midwifery Council, 2021)
Objective: To test the effect of the preparatory information provision program on anxiety in patients undergoing brain tumor surgery. Design: Two-group quasi-experimental research with a pre-test and a post-test. Methodology: The samples consisted of patients undergoing brain tumor surgery and admitted to a neurosurgery ward of a tertiary hospital between April and September 2020. The samples were randomly assigned to the control and experimental groups, 27 cases per group. The experimental group received the Preparatory Information Provision Program developed by the researchers, including a video and booklet by applying self-regulation theory as a conceptual framework. And the control group received routine nursing care. Data collection tools included the personal and health information record form, the State-Trait Anxiety Inventory. The personal and health data were analyzed using descriptive statistics. Compare the anxiety scores using the Wilcoxon Signed Ranks Test and Analysis of Covariance (ANCOVA). Results: The results showed that the anxiety scores were statistically signifcantly lower after receiving the Preparatory Information Provision Program (p=.001). The anxiety scores of the treatment group were statistically signifcantly lower than the control group (p=0.000). Recommendations: Nurses can apply the Preparatory Information Provision Program to fit with institutional context to reduce patients' preoperative anxiety. Future research can examine the effects of the program on postoperative and pre-discharge anxiety.